Le Fort Fractures: A Narrative Review of Diagnosis and Management - Madani, Amanda Refa; I Gede Sutawan (Nusantara Medical Science Journal, 2025)
Le Fort fractures represent complex midfacial fracturestypically resulting from high-velocity trauma,characterized by the separation of the maxillary structurefrom the cranial base. This narrative review synthesizescontemporary literature regarding the etiopathogenesis,classification, diagnosis, and management of thesefractures. Diagnosis requires a comprehensive clinicalassessment supplemented by non-contrast computedtomography (CT) as the gold standard for delineatingfracture patterns and buttress involvement. The reviewdiscusses the clinical relevance of classical Le Fortclassifications alongside Wassmund and Marcianimodifications to guide surgical planning. Managementstrategies prioritize initial stabilization according toAdvanced Trauma Life Support (ATLS) principles,particularly airway control, followed by definitive surgicalintervention. Open reduction and internal fixation (ORIF)remains the primary surgical modality, focusing on therestoration of vertical and horizontal buttresses,occlusion, and orbital integrity. Postoperative care iscritical for preventing complications such as infection,malunion, and ocular dysfunction. Ultimately, successfulmanagement necessitates a multidisciplinary approachcombining precise imaging and rigid fixation to restorefacial aesthetics and function while minimizing long-termmorbidity.